Dynamics of Interaction Between Law and Socio-Culture In The Context of A Multicultural Society - Pasya Ashsyafa, Zaen; Sari, Wulan; Amalya Rahayu, Putri; Dikrurahman, Diky; Yusup Permana, Deni (Ridwan Institute, 2024)
In a multicultural society, the interaction between law and socio-cultural factors has a significant impact on people's daily lives. Various social and cultural norms, values and practices often collide with applicable legal principles, causing complex dynamics in law enforcement and the implementation of justice. This research aims to analyze the dynamics of interaction between law and socio-cultural factors in a multicultural society. This study used qualitative research methods. The data collection technique in this research is literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that the interaction between law and social culture is complex and dynamic. Law can influence social culture and vice versa. Law can influence social culture by encouraging social change and preserving culture. Meanwhile, social culture can influence law by forming norms and values and influencing law enforcement.